المعالجة الموضعية لمرضى الصداف الشائع بالموميتازون فوروات والكالسيبوتريول (دراسة مقارنة/ خبرة مشفى الأسد الجامعي باللاذقية) - دلول, محمود; الخيًر, عبد الله; الأطرش, رزان (Latakia University Journal -Medical Sciences Series, 2019)
الصداف مرض التهابي مزمن معاود يصيب الجلد والفروة والمفاصل، يكون شديداً أو خفيفاً. الصداف الشائع هو أكثر أنماط الصداف مشاهدة. تعتبر مراهم الكالسيبوتريول والموميتازون فوروات من المعالجات الموضعية الشائعة الاستخدام في الصداف الشائع، مع أن آلية تأثيرها مختلفة. تمت مقارنة الفعالية السريرية لمشاركة الدواءين مع بعضهما ولكل منهما على انفراد. تم توزيع المرضى الـ 120 وبشكل عشوائي على ثلاث مجموعات متساوية، عولج المرضى في كل مجموعة لمدة 4 أسابيع إما بمرهم الكالسيبوتريول أو بمرهم الموميتازون فوروات أو بمشاركة المرهمين معاً. أدت المعالجةإلى إنقاص شدة PSAI في نهاية المعالجة بمعدل 73.62 % في مجموعة المشاركة و 46.5 % في مجموعة الكالسيبوتريول و 57.5% في مجموعة الموميتازون. وكان معدل التراجع بعد أسبوعين 52.53 % 34 % و 42.6 % على التوالي. أظهرت المعالجة المشاركة بأنها أكثر فعالية وأقل تأثيرات جانبية من المعالجة المفردة بأي من الدواءين. Background: Psoriasis is a chronic and recurrant inflammatory disease that affects the skin, scalp, and joints. It ranges in severity from mild to severe. Psoriasis vulgaris is the most common typ of disease. Calcipotriol and mometasone furoate are common topical treatments used for psoriasis vulgaris, with different mode of action. Objective: We compared the clinical efficacy of the combination of the two agents with each other alone. Methods: 120 patient were randomly placed in three groups and treated topicaly along 4-weeks with either calcipotriol ointment 50 µg/g, mometasone furoate ointment 0,1 %, or a combination of the two agents together. Results: The mean percentage reduction in PASI from baseline to end of treatment was 73,62% in the combination group, 46,5% in calcipotriol group, and 57,5% in mometasone group. The reduction after two weeks was 52,53%, 34%, and 42,6% respectively. Conclusion: The combination therapy shows superior efficacy and less side effects compared with the singel therapy.